Immersion studies of Al2O3 – 13% TiO2 and Cr2O3 coatings on ship hull plate in simulated seawater environment in laboratory. (2022) - Raj Sharma, Aaishwarika; Goyal, Rakesh
Abstract: In the present work the corrosion behaviour of Al2 O3 – 13% TiO2 and Cr2 O3 coatings in an artificial seawater environment is investigated by immersion test and weight measurement methods. The coatings are deposited on ship hull steel by D-Gun flame spray method. The microstructure and phase composition of coatings are studied by scanning electron microscopy (SEM) and electron dispersive spectrum (EDS). The corrosion resistance of coatings is compared on the basis of weight measurement and visualization technique. The change in microstructure and elemental phase composition is also observed by the corroded micrographs.